Analysis dimension of quantitative reasoning and cooperative learning - RICRA-MAYORCA, JUAN MANUEL; GARCÍA-CHAUCA, JENIFFER DORIS; ROMERO-FLORES, LISSETH ANGELA (LACCEI, 2024)
The aim of this study was to establish the correlation between cooperative learning and the analytical aspect of quantitative reasoning in university students. The research pertains to a study that employs a quantitative methodology, specifically a correlational level and a non-experimental cross-sectional design. The sample comprised 121 students from a private institution in Lima. A 29-item questionnaire was utilized to assess cooperative learning, whereas the evaluation of the quantitative reasoning analytical dimension was conducted in an authentic scenario using a rubric. The findings demonstrated a notable correlation between cooperative learning and the dimension analysis of quantitative reasoning.